2020
DOI: 10.1038/s41598-020-74794-3
|View full text |Cite
|
Sign up to set email alerts
|

Technical considerations when designing a gene expression panel for renal transplant diagnosis

Abstract: Gene expression analysis is emerging as a new diagnostic tool in transplant pathology, in particular for the diagnosis of antibody-mediated rejection. Diagnostic gene expression panels are defined on the basis of their pathophysiological relevance, but also need to be tested for their robustness across different preservatives and analysis platforms. The aim of this study is the investigate the effect of tissue sampling and preservation on candidate genes included in a renal transplant diagnostic panel. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Although the NanoString platform offers the most affordable and technically robust method of performing multiplexed expression analysis on the limited, low-quality RNA isolated from FFPE tissue, a subset of transcripts do not correlate between NanoString and quantitative real-time polymerase chain reaction (qRT-PCR) or are affected by tissue handling (FFPE tissue vs. tissue that is fresh frozen or placed in RNAlater). 35,36 Upcoming validation studies with an increased sample size will aim to determine if histologic parameters, such as severity of tubulitis and mast cell numbers, and transcriptionally detected alterations in allograft lipid metabolism are predictive of CA TCMR treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NanoString platform offers the most affordable and technically robust method of performing multiplexed expression analysis on the limited, low-quality RNA isolated from FFPE tissue, a subset of transcripts do not correlate between NanoString and quantitative real-time polymerase chain reaction (qRT-PCR) or are affected by tissue handling (FFPE tissue vs. tissue that is fresh frozen or placed in RNAlater). 35,36 Upcoming validation studies with an increased sample size will aim to determine if histologic parameters, such as severity of tubulitis and mast cell numbers, and transcriptionally detected alterations in allograft lipid metabolism are predictive of CA TCMR treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…We did not test in this study whether the AMR 10-gene score is applicable using other techniques, or other sample types, such as formalin-fixed paraffin-embedded tissue. However, in another manuscript where we investigated whether results of gene expression analysis performed using qRT-PCR on samples preserved in RNAlater correlated with results using Nanostring nCounter analysis on formalin-fixed paraffin-embedded tissue, these 10 genes correlated well [ 15 ]. We previously observed that there was good correlation between measurements of AMR-associated genes, when comparing two different cores from the same kidney transplant, using two different techniques (Nanostring and qRT-PCR) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was carried out using an Applied Biosystems Vii7 real-time qPCR machine [ 8 ]. Gene-specific primers spanning an intron were designed for 18 genes from a list of ‘top hits’ for AMR in the literature ( Supplementary data, Table S1 ) [ 1–3 , 5 , 8 , 10 , 14 , 15 ]. Gene expression levels were normalized to housekeeping gene HPRT1 and results were measured relative to Stratagene qRT-PCR Reference RNA (Agilent Technologies using the ΔΔCt method) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…This has enabled the ability to perform RNA analyses using the aforementioned microarray techniques or bulkSeq. Despite this advancement, which opens the door for in-depth, retrospective analyses of preserved samples, formalin fixation of the tissue may lead to inferior RNA quality ( 64 , 65 ), producing artificial associations and overrepresentation of histone transcripts ( 66 ).…”
Section: Bulk Rna Sequencingmentioning
confidence: 99%